Studies on suitability of existing climbing devices for palmyrah palm (Borassus flabellifer L.) - Vengaiah, P.C.; Murthy, G.N.; Maheswarappa, H.P. Maheswarappa (Journal of Plantation Crops, 2018)
Please refer the pdf fulltext.